Participation in farm markets in rural Northwest Pakistan: A regression analysis - Inayatullah Jan (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2012)
Participation in farm markets is important for increasing income of farmers in the developing countries. A number of factors account for a household participation in agricultural marketing. This study attempts to explore such associated factors which play a significant role in farmers' participation in farm markets in rural northwest Pakistan. Drawing on empirical data from the field survey; gur, vegetables, and milk were the main products offered for marketing in the area. The degree of specialization of market relations was based on the nature of the farm product. In gur markets, the marketing relations were based on personalized terms whereas in vegetable markets, they were exclusively commercialized. The results of the binary logit model show that size of selfcultivated land and number of livestock, were important determinants of a household participation in agricultural marketing. The study concludes that participation in agricultural markets could be substantially increased through improved infrastructure, commercialized farming systems, and increased number of farm markets so that the dominance of few selected commission agents is minimized.
Keywords: 330; Agricultural marketing; Farm products; Commission agent; Gur; Logit model